Resistência de união de cimentos resinosos a dentina afetada por cárie - Godas, André Gustavo de Lima [UNESP] (2010)
The aim of this study was to evaluate the microtensile bond strength of conventional and self-etch resin cements to hygid or caries-affected dentin, 24 hours after the bonding procedure. Crows of Tescera (Bisco) indirect resin-based composite were bonded to hygid or caries-affected dentin using three different resin cements: RelyX ARC (3M Espe), Panavia F (Kuraray) and RelyX Unicem (3M Espe). The microtensile bond strength was measured in a universal testing machine (Emic) 24 hours after the bonding procedure. The data were submitted to two-way ANOVA and PLSD Fisher's test (p=0.05). The RelyX ARC showed the highest values of microtensile bond strength compared with the other resin cements, for both dentin conditions (p<0.001). For both substrates, there is no difference among Panavia and RelyX Unicem (p<0.05). Independent of the resin cement, there is no difference between hygid and caries-affected dentin (p=0.8935). Based on the results of this study, we can conclude that the bonding procedure of resin cements to dentin is more dependent of the resin cement used than the condition of the dentin tissue